2017
DOI: 10.19173/irrodl.v18i1.2630
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and the Building of Learning Communities: An Experimental Study of a Social MOOC

Abstract: This study aimed to analyze the student's behaviour in relation to their degree of commitment, participation, and contribution in a MOOC based on a social learning approach. Interaction data was collected on the learning platform and in social networks, both of which were used in the third edition of a social MOOC course. This data was then studied via statistical methods and analysis of social networks.This study assumes that social communities would arise around the course, would remain over time, and that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…These results are consistent with those found by authors such as Lima and Zorrilla (2017), and in line with their argument, we conclude that cultural variables may have influenced these results: in Spanishspeaking countries, student behaviour is regulated so by teacher leadership and consideration as a source of reinforcement than by socialization with peers. As noted by Alhazmi and Rahman (2014), it is important to bear in mind that social networking sites by themselves cannot explain student commitment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with those found by authors such as Lima and Zorrilla (2017), and in line with their argument, we conclude that cultural variables may have influenced these results: in Spanishspeaking countries, student behaviour is regulated so by teacher leadership and consideration as a source of reinforcement than by socialization with peers. As noted by Alhazmi and Rahman (2014), it is important to bear in mind that social networking sites by themselves cannot explain student commitment.…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note that despite having found that social media use facilitates student participation, some reports indicate that the networks generated in this context do not constitute stable communities of practice, since students stop using the social networking site once the academic activity is over, at which point the teacher becomes no longer involved in the interaction (Lima & Zorrilla, 2017). These authors have suggested that in Spanish-speaking countries, student behaviour is regulated by teacher leadership and consideration as a source of reinforcement (Lima & Zorrilla, 2017). By themselves, networks alone do not reinforce student commitment; instead, this may be influenced by a multitude of factors (Alhazmi & Rahman, 2014).…”
Section: Literature Reviewmentioning
confidence: 97%
“…For instance, in MOOCs, learning behaviour includes the frequency of watching video lectures, the number of posts in online discussion forums, and the number of assignments completed and submitted (Wei et al, 2021 ). Assessment of learning behaviour can reveal students’ level of engagement in learning, their strategies for coping with particular tasks, and their behavioural patterns that may explain certain learning outcomes (de Lima & Zorrilla, 2017 ; Lee, 2019 ). The affective domain refers to students’ perceptions and attitudes related to learning, including course satisfaction, perceptions of learning experiences, and perceptions of how certain learning experiences affect their confidence, motivation, self-efficacy, sense of progress, and so on (Wei et al, 2021 ).…”
Section: Online Assessment Practice: Objects Methods and Utilisationmentioning
confidence: 99%
“…Aspects in the affective evaluation include 1) student satisfaction in learning or evaluation in learning; 2) perceptions of learners' learning experiences in learning; 3) the learning benefits felt by students [50]. Student satisfaction is measured by the realization of learning objectives [51]. Students will feel a higher level of satisfaction from peer interactions such as support from friends and sharing with other students.…”
Section: Alternative Affective Assessment Approaches Civic Learningmentioning
confidence: 99%